Arquitetura para uma nova escola: modernização da arquitetura escolar de João Pessoa (1930-1939) - Oliveira, Marina Goldfarb de (2013)
The main goal of this work is to study how was the developing of the modernization of the scholar architecture on João Pessoa in the 1930 years, with the adoption of the ideas of the New School pedagogic movement. In this sense, was selected for analysis the educational complex corresponding to the once called Institute of Education of Paraíba, formed by three buildings: the Central Building (where was promoted the secondary school and teacher's formation), the "Infancy Garden" and the "School of Application". This institution was planned as a model of the educational system of the Paraíba, predicted by the Plan of Reform of the Public Institution in 1935, which proposed new directives for the construction of new scholar buildings. This work is organized in three chapters, where the first presents how was the scholar environment in João Pessoa before the existence of an architecture specific for educational purposes and how was the first schools built to this end; the second chapter presents the new scholar architecture that toke place with the educational reforms in Rio de Janeiro, São Paulo and Paraíba, whose directives were based on the two first States; the third chapter analyzes the buildings of the “Institute of Education of Paraíba” and its architecture through the relation of the pedagogic ideas of the movement “New School” with the modernization of the scholar environment.